Comparison of Temporary Waste Storage (TPS) Management at Community Health Centres (Puskesmas) with TPS Standards - Rachma, Riski Allivia; Inayah, Zufra; Mindiharto, Sestiono; Budiono, Nugrahadi Dwi Pasca (Yayasan Ahmad Mansyur Nasirah, 2025)
The condition of Temporary Waste Storage (TPS) facilities in community health centres (Puskesmas) across Tuban Regency still requires particular attention, as only 24% of them currently possess an integrated Environmental Management Statement Letter (SPPL) issued by the Department of Environment and Transportation (DLHP). This study aims to analyse the comparison of TPS management in Puskesmas against the applicable standards in 2024. It is an observational survey study using a quantitative approach. The study population consisted of 33 Puskesmas in Tuban Regency, with a sample of 8 inpatient Puskesmas and 6 outpatient Puskesmas that already have an integrated SPPL. The research instruments covered various stages of waste management, including waste segregation, storage, transportation, personal protection, and the volume of medical waste generated. Data were analysed using Fisher’s Exact Test. The results showed that the majority of inpatient Puskesmas (75%) met the TPS standards, as did most outpatient Puskesmas (83.3%). The highest amount of medical waste was found in inpatient Puskesmas, with an average of 139.38 kg, while outpatient Puskesmas produced an average of 68.83 kg. In conclusion, TPS management in Puskesmas within Tuban Regency in 2024 has generally complied with current regulations. Improving existing infrastructure and updating Standard Operating Procedures (SOPs) are essential to support more effective hazardous waste (B3) management and to reduce the volume of waste generated.